Alterations of pr-M Cleavage and Virus Export in pr-M Junction Chimeric Dengue Viruses - Keelapang, Poonsook (American Society for Microbiology, 2004)
During the export of flavivirus particles through the secretory pathway, a viral envelope glycoprotein, prM, is cleaved by the proprotein convertase furin; this cleavage is required for the subsequent rearrangement of receptor-binding E glycoprotein and for virus infectivity. Similar to many furin substrates, prM in vector-borne flaviviruses contains basic residues at positions P1, P2, and P4 proximal to the cleavage site; in addition, a number of charged residues are found at position P3 and between positions P5 and P13 that are conserved for each flavivirus antigenic complex. The influence of additional charged residues on pr-M cleavage and virus replication was investigated by replacing the 13-amino-acid, cleavage-proximal region of a dengue virus (strain 16681) with those of tick-borne encephalitis virus (TBEV), yellow fever virus (YFV), and Japanese encephalitis virus (JEV) and by comparing the resultant chimeric viruses generated from RNA-transfected mosquito cells. Among the three chimeric viruses, cleavage of prM was enhanced to a larger extent in JEVpr/16681 than in YFVpr/16681 but was slightly reduced in TBEVpr/16681. Unexpectedly, JEVpr/16681 exhibited decreased focus size, reduced peak titer, and depressed replication in C6/36, PS, and Vero cell lines. The reduction of JEVpr/16681 multiplication correlated with delayed export of infectious virions out of infected cells but not with changes in specific infectivity. Binding of JEVpr/16681 to immobilized heparin and the heparin-inhibitable infection of cells were not altered. Thus, diverse pr-M junction-proximal sequences of flaviviruses differentially influence pr-M cleavage when tested in a dengue virus prM background. More importantly, greatly enhanced prM cleavability adversely affects dengue virus export while exerting a minimal effect on infectivity. Because extensive changes of charged residues at the pr-M junction, as in JEVpr/16681, were not observed among a large number of dengue virus isolates, these results provide a possible mechanism by which the sequence conservation of the pr-M junction of dengue virus is maintained in nature.